THE EFFECT OF TEMPERATURE AND ADDITION OF CAO TO HYDROGEN PRODUCTION FROM PATTUKKU COAL CHAR GASIFICATION (Universitas Negeri Semarang, 2017)
Hydrogen is an environment-friendly fuel and has a high caloric value. Hydrogen as a molecule is not found in nature, but it is found in compounds with other elements. Besides catalytic steam reforming of natural gas, hydrogen can also be produced from thermochemical processes such as combustion, pyrolysis, and gasification. The process of gasification using steam as gasification agent can increase the yield of H2 in the gas products. The objectives of this research are to study the influence of temperature and the addition of CaO on H2 production. This research was conducted in an up-draft reactor for 60 minutes with three different temperatures; i.e. 600, 700, and 800 oC and ratio of CaO:char of 0 and 0.5. Based on this study, the rise of temperature will improve the yield of H2 and CO2 in the gas products. At gasification temperature of 800 oC, the yield of H2 and CO2 is maximum. Moreover, the addition of CaO can improve the char conversion and reduce the concentration of CO2 in the gas products.